Analysis of the features of the strategic potential of the development of enterprises in the construction industry - Harnam, M. (Ways to Improve Construction Efficiency, 2018)
According to the results of the analysis of the theoretical foundations of capacity management, the main directions of research of the strategic potential of the development of enterprises in the construction industry are identified. This made it possible to determine the factors of the external environment of construction companies, the peculiarities of the development of their strategic potential, the main tasks of the strategic potential management system. Proposals for the creation of a system of organizational knowledge, information and analytical support for assessing the strategic potential of development of construction companies, taking into account the specifics of their activities. The measurement of strategic potential should include an assessment of all its components, taking into account the defining and different in nature factors: the level of achievement of enterprise goals, efficiency of functional areas, the ability of the management system to progressive self-improvement and self-development, etc.